The old Latin manuscripts of the Gospel of Luke: a new edition of the Codex Vercellensis Luke based on multi-spectral images - Weissenrieder, Annette; Visinoni, André Luiz (Arbeiten zur neutestamentlichen Textforschung, 2024)
The Codex Vercellensis is one of the great treasures of the Vercelli library, containing the four Gospels. Written during the fourth century, it is the oldest remaining Latin manuscript of the Greek New Testament and one of the most important witnesses to the early understanding of the Gospels. In this edition, Weissenrieder and Visinoni provide the Latin text of the work parallel to spectral images, indicating abbreviations, lineation, foliation and staurograms as well as a (reconstructed) critical edition with references to the most important texts of the Old Latin tradition as well as Greek and Syriac manuscripts and a commentary to this unique Latin translation. The analyses involved will be: (1) digital methods, (2) philological and theological, (3) translation theories in antiquity as well as (4) genealogical. The authors call into question assumptions about the text preserved in the manuscript, arguing that it represents an early stage of the Latin Gospels. The manuscript will be examined in light of its wide-ranging cultural and historical context. As such, the project aligns itself methodologically with the field of manuscript studies and attempts to integrate the specialized expertise of various disciplines in the study of a single object